Analisis Semantik dan Pragmatik Terhadap Hadis-Hadis Penentuan Awal Bulan Hijriyah dan Implikasi Hukumnya - Zubair; Ahmad, Arifuddin; Fatmal, Abd. Bashir (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2025)
This study investigates how linguistic analysis influences Islamic legal construction in determining the beginning of Hijri months, particularly when the crescent is not visible. It focuses on three variant hadith formulations, fa in gumma, fi in gummiya, and fa in gubbiya; imperative word ṣūmū and afṭirū based on ru’yah; and the paired imperatives faqdurū lah and fa akmilū. The research employs a qualitative design using semantic and pragmatic analysis, supported by lexical, morpho-syntactic examination and Uṣūl al-Fiqh reasoning. Primary data are drawn from authoritative hadith compilations, while supporting evidence is taken from classical Arabic lexica and contemporary astronomical discussions. The findings show that ru’yah is polysemous and cannot be restricted to sensory sight alone; it also denotes epistemic certainty. The wording gumma/gummiya indicates external obscuration and corresponds to faqdurū, which semantically implies precise measurement, thus providing linguistic support for astronomical calculation (ḥisāb). In contrast, gubbiya reflects informational limitation and reinforces istikmāl as an operational legal mechanism. This study argues that hisab and istikmāl are not mutually exclusive but complementary, and they may be operationalized through imkān al-ru’yah computation with tolerance for local, regional, or global maṭla’. These results offer a linguistic basis for integrating fiqh and astronomy in authoritative lunar-month determination.